The Effect Of Combination Of Progressive Muscle Relaxation And Mckenzie Neck Exercise On Intensity Pain Cases Of Myofascial Pain Syndrome Upper Trapezius Muscle On Students - Nor Adha Luthfia Afifa; Nungki Marlian Yuliadarwati (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Background: Students often use gadgets for learning needs for a long time, and most of them do not pay attention to ergonomic body positions and tend to be in a static state. This causes tension in the muscles around the neck and shoulders that triggers point, resulting in myofascial pain syndrome in the upper trapezius muscles. This has an impact on student productivity. Objective: to determine the effect of the combination of progressive muscle relaxation and mckenzie neck exercise on the pain intensity of upper trapezius muscle myofascial pain syndrome in college student. Methods: this study used a pre-experimental design (one group pre-test and post-test). The subjects of this study were KM-HSS students in malang area, totaling 20 people. This research was conducted for 14 days in 2 times a day. The measuring instrument in this study used the Numerical Rating Scale (NRS) as a pain scale measuring instrument. Results: this study showed that there was a significant effect before and after being given a combination exercise on pain intensity in myofascial pain syndrome on the upper trapezius with p = 0.000 (p<0.005). Conclusion: There is an effect of a combination of progressive muscle relaxation an mckenzie neck exercise on the pain intensity of myofascial pain syndrome cases of upper trapezius muscle in KM-HSS students in the Malang area.